2011
DOI: 10.1203/pdr.0b013e31822e178e
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Hemodynamic and Metabolic Effects of Vasoactive Medications in Normotensive, Anesthetized Neonatal Piglets

Abstract: ABSTRACT:The developmentally regulated hemodynamic effects of vasoactive medications have not been well characterized. We used traditional and near-infrared spectroscopy monitoring technologies and investigated the changes in heart rate, blood pressure, common carotid artery (CCA) blood flow (BF), cerebral, renal, intestinal, and muscle regional tissue O 2 saturation, and acid-base and electrolyte status in response to escalating doses of vasoactive medications in normotensive anesthetized neonatal piglets. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 31 publications
2
32
0
1
Order By: Relevance
“…Although this was a setback, the rate of low SVC flow reported in this study is in accordance with recent publications. 18 These preliminary results support a significant effect of DB on HR, as has been shown in mature newborn animals 19 and small observational studies in neonates. 20 DB administration did not raise any safety issues in this context, because no dose-limiting effects were observed during the study.…”
Section: Discussionsupporting
confidence: 80%
“…Although this was a setback, the rate of low SVC flow reported in this study is in accordance with recent publications. 18 These preliminary results support a significant effect of DB on HR, as has been shown in mature newborn animals 19 and small observational studies in neonates. 20 DB administration did not raise any safety issues in this context, because no dose-limiting effects were observed during the study.…”
Section: Discussionsupporting
confidence: 80%
“…Another possible limitation of the present study has been the exclusion of patients on vasoactive drugs. In experimental and clinical studies, it has been shown that these drugs, depending on the dosage, can cause relevant alterations in the register of the mean regional tissue perfusion measured by NIRS [29,30]. This situation was especially common in patients with lower GA in whom it was extremely difficult/impossible to place the abdominal sensor.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some of the studies showed an increase in heart rate in a dose-dependent manner [5], [9], [11][13], [16], [18], [23], [26], [28]. An increase in stroke volume was mainly observed in studies using prolonged infusion (from 2 to 6 h) at doses higher than 10 µg/kg/min [6], [8], [9], [17].…”
Section: Resultsmentioning
confidence: 84%
“…In general, although studies were conducted in different animal species, more than 62% of them were performed in pigs [5][19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation